When the mall is in the airport: Measuring the effect of the airport mall on passengers' consumer behavior. (September 2018) - Castillo-Manzano, José I.; López-Valpuesta, Lourdes; Sánchez-Braza, Antonio
Abstract: This paper provides a new approach to evaluating the influence on passenger F&B consumption and expenditure of terminals that approximate to the concept of an airport shopping mall. Using a broad database of 37, 226 passengers interviewed at eight different Spanish airports, including two Spanish hub airports, Madrid-Barajas and Barcelona, with a methodology framed within statistical causal inference with Kernel and Radial matching, the results robustly demonstrate that passengers alter their consumption behavior in hub airport malls compared to how they behave at regional airports with a smaller commercial and F&B offer. Specifically, there is an increase of between 3.7 and 4.1% in the likelihood that hub passengers will make a consumption and between 1.2 and 1.3% in the likelihood that they will make a purchase, while mean per-passenger spending increases by 3.53€. Highlights: An airport mall increases the likelihood that passengers make a consumption by 3.7–4.1%. The greater commercial offer in a hub increases the likelihood of passengers making a purchase by between 1.2% and 1.3%. Those passengers who really make an expenditure increase their spending by some 5.40 € at hubs over regional airports. The mean expenditure at hubs exceeds that at regional airports by between 3.52 € and 3.54 € on average. This research will help justify the price charged on concession at the two different types of airport.